Konsep Qath’i dan Zhanni dalam Hukum Kewarisan Islam (UINSI Samarinda, 2016)
The term qath'i (definitive) and zhanni (speculative) in Usul al-Fiqh is used to explain the sources of Islamic legal texts either the Qur'an or Hadith in two ways, namely al-tsubût (existence) or al-wurud (sourced from the truth), and al-dalalah (textual implication). In terms qath'i and zhanni al-tsubut and al-wurud, Islamic jurists agree that the Koran and the hadith mutawatir is definitive, whereas ahad hadith is zhanniy ats-tsubut. They differ in terms of qath'i and zhanni of the al-dalalah (interpretation). Islamic jurists state that if a text of the Koran or Hadith contains only one meaning that is clear and not open up to other possible interpretations, as well as read certain numbers, then the text is regarded as the definitive text of textual implication. The texts relate to inheritance law fall into the category this qath`i al-dalalah. Meanwhile, contemporary Islamic jurists state that the qath'i and zhanni al-dalalah of the texts both the Koran and the hadith cannot be seen from the clarity of meaning of the texts but also on the desired essence of the text which is commonly known as the maqasid al-shari'ah. The maqasid approach must also be coupled with the theory ta'abbudi and ta'aqquli. Based on this, this article argues that the texts related to Islamic inheritance law is categorized zhanni al-dalalah because they concern of human social relations (mu`amalah) which are affected by the socio-economic context of the role of men and women in society (ta`aqquli). Consequently, the texts in the field of inheritance law are open to modern interpretations.Keywords: Islamic inheritance law, qath'i and zhanni in Islam